How elephants lost their wings. - Sims, lesley; Lovell, Katie (london Usborne publishine ltd, 2007)
Believe it or not, elephants used to be able to fly. But flying elephants were big trouble ... Simply written in lively, flowing text Usborne First Reading books are designed to capture the imagination and build the confidence of beginner readers. This book includes audio, simple comprehension puzzles and downloadable worksheets and teacher's notes. ""For every parent, child and teacher weary of the monotony of the average reading scheme, Usborne's First Reading series will offer rays of sunlight. The books are carefully levelled and offer a huge variety of accessible and fun, fiction and non-